Professional knowledge construction through reflective practice and tutorial supervision - Campos, Joana (2010)
In this paper the implications of the primary school teachers’ education model implemented at the School of Education of Santarém from 2001 up till now are analysed with respect to the perceived implications of the experienced model on their professional knowledge and practice as beginner teachers. The focus of the research goes to the procedures of reflective analysis, feedback and supervision developed during the practicum throughout the whole training curriculum. Some data are presented and analyzed from a longitudinal exploratory study that has been developed focusing on a sample of beginner teachers who experienced the model, initiating their activity: a) Analysis of individual written reflections produced regularly by students (5 per year), within the practicum, and of their interaction with written feedbacks provided by the supervisor’s team on those reflective writings; b) Semi-structured interviews to a smaller sample within this group in order to deepen the understanding of the same issues. - No presente artigo procura dar-se conta dos resultados encontrados pela pesquisa desenvolvida sobre o impacto do modelo de formação implementado na Escola Superior de Educação de Santarém desde 2001, designadamente no curso de Professores do Ensino Básico- 1º Ciclo, no que se refere ao desenvolvimento de uma prática profissional reflexiva e construção do conhecimento profissional. O foco analítico incide sobre os procedimentos relativos à análise reflexiva, ao feedback a essa análise e à supervisão desenvolvida no âmbito do curso de formação inicial.Os dados apresentados resultam de um estudo exploratório longitudinal desenvolvido em torno de um grupo de sujeitos que à época do primeiro estudo se encontravam a frequentar o curso de formação inicial, e que no segundo estudo se encontravam já em início de carreira. Metodologicamente foram analisados os textos escritos de autoria dos alunos, as reflexões, produzidas no âmbito da iniciação à prática profissional, assim como os feedbacks dos supervisores responsáveis pelos estágios (estudo 1). Complementarmente realizaram-se entrevistas aos professores em início de carreira (estudo 2) seleccionados a partir do grupo de sujeitos do estudo anterior.